The limits of articulation of the anti-minning movements in Peru - Ruiz, Gabriela (2013)
The present article discusses the enviromental conflicts related to the mining during the recent past years, with the purpose of identify the limits and the difficulties that have been present in the articulation of a national anti-mining social movement in Peru. The questioning about the reach of the anti-mining movement arises from the constants outbreaks of conflicts that are determinate by local dynamics. The confrontation between the mining company and peasant´s communities has been occurring in different areas of the country, and that is why the analysis focuses in the cases of the ‘Aymarazo’ in Puno, Conga in Cajamarca, and the contrast of informal mining in Madre de Dios. The analysis of the cognitive frameworks, the structure of organization, the window of opportunities, allow this work to recognize the character of the anti-mining mobilizations that occurs in every conflict.